Entre a arte e a técnica: o dilema do social nas agroindústrias familiares rurais no município de Constantina/RS - Sulzbacher, Aline Weber (2009)
This dissertation has the aim of presenting an evaluation proposal on the social impact of the rural family agro-industry, using as analysis scales the unity of production and the community environment. The proposal itself is a set of variants and indexes which can be used to discuss and measure the social dimension of the family agro-industry. In this study context, the social dimension is adjusted since the improvement of the life quality of the rural subjects involved in the process. However, this is not a reality to all agro-ndustrialization experiences, and several end up dealing with both negative and positive social impacts, mainly to the family group. To develop the research, a theory study was conducted, on the social impact evaluation and, from this basis; the first proposal took place presenting a series of variants and indexes which, furthermore, were used to reflect about the possible social impacts of some agro-industrialization experiences in the county of Constantina/RS. The evaluation proposal of the social impact was re-elaborated through the inclusion and/or exclusion of variants, indexes and hypothesis of the impacts. This process resulted of a social impact evaluation proposal that holds 25 variants with 56 indexes. The field incursions indicated that the most significant social impacts can be perceived through the work, income and education variants when dealing with the family production unity scale, and the food safety variant when dealing with the community environment. Overall, the results lead to a process in which the negative social impacts tend to be more significant when the agro-industry starts to be the main activity of the family production unity, demanding production scale and a strengthening of the workforce. So, between art and technique would be some of the social dilemmas faced at the heart of the agro-industrializations processes, once they illustrate a transition process between the artisanal production that generates a complementary income, and the family agro-industry that becomes the main source of income of the family group.